2021
DOI: 10.1097/mpa.0000000000001846
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation by Endosonographer of Endoscopic Ultrasound Fine-Needle Aspiration of Solid Pancreatic Lesions

Abstract: Objectives: Rapid on-site evaluation (ROSE) by cytopathologists during endoscopic ultrasound-fine-needle aspiration (EUS-FNA) of solid pancreatic lesions (SPLs) improves adequacy and diagnostic accuracy while reducing the number of needle passes. We evaluated the usefulness of ROSE performed by the endosonographer.Methods: Patients with an SPL were randomly assigned to EUS-FNA with ROSE or non-ROSE. Procedure duration, number of needle passes, specimen adequacy, and adverse event rates were compared.Results: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“… 25 Several studies assessed the performance of endoscopists or endosonographers in assessing the diagnostic adequacy of EUS-FNA samples and demonstrated a higher diagnostic adequacy among these endoscopists or endosonographers. 21 , 26 , 27 However, the training curriculums varied in different studies, leading to a considerable inconsistency between endoscopists and cytopathologists. 28 To the best of our knowledge, no studies have implemented deep learning in assessing the diagnostic adequacy of EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Several studies assessed the performance of endoscopists or endosonographers in assessing the diagnostic adequacy of EUS-FNA samples and demonstrated a higher diagnostic adequacy among these endoscopists or endosonographers. 21 , 26 , 27 However, the training curriculums varied in different studies, leading to a considerable inconsistency between endoscopists and cytopathologists. 28 To the best of our knowledge, no studies have implemented deep learning in assessing the diagnostic adequacy of EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, HP diagnosis of solid pancreatic tumors was performed by EUS–FNA, through cytological examination, direct smears, cytospin [ 14 ]. Rapid on-site evaluation (ROSE) was also proposed to faster analyze the smears and repeat the EUS–FNA if necessary [ 15 ]. However, randomized studies have shown that this approach may not be so efficient, and it does not significantly improve EUS sampling resultant [ 16 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…However, data are limited, being mainly retrospective studies [2][3][4] with only two randomized trials that did not directly assess clinical outcomes. 5,6 In this issue of Journal of Gastroenterology and Hepatology, Zhang et al reported the results of a single center randomized trial that compared the diagnostic performance of EUS-FNA with and without self-ROSE. 7 The endoscopists underwent a 1 month training in sample adequacy assessment and cytopathological diagnosis of EUS-FNA pancreas cytology in the pathology department.…”
mentioning
confidence: 99%
“…Self-ROSE resulted in significantly shorter mean procedure time (30 vs 37 min, P < 0.005) and fewer mean number of needle passes (2.6 vs 3.5, P < 0.005). 6 The structure of a valid training curriculum for self-ROSE and the minimum level of expertise to be achieved and maintained are two very important issues that need to be addressed. The definitive cytological diagnosis must always be provided by a pathologist as it is unreasonable to expect endoscopists to have equivalent level of proficiency.…”
mentioning
confidence: 99%